Case Reports: Bronchial Mucosal Vasculature Is Also Involved in the Acute Vascular Distress Syndrome of COVID-19 - Jounieaux, Vincent; Basille, Damien; Toublanc, Bénédicte; Andrejak, Claire; Rodenstein, Daniel Oscar; Mahjoub, Yazine (Frontiers in Medicine, 2021)
Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which targets the pulmonary vasculature is supposed to induce an intrapulmonary right to left shunt with an increased pulmonary blood flow. We report here what may be, to the best of our knowledge, the first videoendoscopic descriptions of an hypervascularization of the bronchial mucosa in two patients hospitalized for coronavirus disease 2019 (COVID-19) pneumonia. Cases Presentation: Two patients, 27- and 37-year-old, were addressed to our Pneumology department for suspicion of COVID-19 pneumonia. Their symptoms (fever, dry cough, and dyspnoea), associated to pulmonary ground glass opacities on thoracic CT, were highly suggestive of a COVID-19 disease despite repeated negative pharyngeal swabs RT-PCR. In both patients, bronchoscopy examination using white light was unremarkable but NBI bronchoscopy revealed a diffuse hypervascularization of the mucosa from the trachea to the sub-segmental bronchi, associated with dilated submucosal vessels. RT-PCR performed in bronchoalveolar lavage (BAL) confirmed the presence of Sars-CoV-2. Conclusions: These two case reports highlight the crucial importance of the vascular component of the viral disease. We suggest that such bronchial hypervascularization with dilated vessels contributes, at least in part, to the intrapulmonary right to left shunt that characterizes the COVID-19 related Acute Vascular Distress Syndrome (AVDS). The presence of diffuse bronchial hypervascularization in the context of COVID-19 pandemic should prompt the search for Sars-CoV-2 in BAL samples.